Clinical and genetic characteristics of 29 Chinese patients with X-linked hypophosphatemia - Xu, Tian; Tao, Xiaohui; Zhang, Zhenlin; Yue, Hua (Frontiers in Endocrinology, 2022)
Objective The aim of this study was to fully describe the clinical and genetic characteristics, including clinical manifestations, intact fibroblast growth factor 23 (iFGF23) levels and presence of PHEX gene mutations, in 22 and 7 patients with familial and sporadic X-linked dominant hypophosphatemia (XLH), respectively. Methods Demographic data, clinical features, biochemical indicators and imaging data of 29 patients were collected. All 22 exons and exon–intron boundaries of the PHEX gene were amplified by polymerase chain reaction (PCR) and directly sequenced. The serum level of iFGF23 was measured in 15 of the patients. Results Twenty-nine patients (male/female: 13:16, juvenile/adult:15:14) with XLH were included. The main symptoms were bowed lower extremities (89.7%), abnormal gait (89.7%), and short stature/growth retardation (78.6%). Hypophosphatemia with a high alkaline phosphatase level was the main biochemical feature and the median value of serum iFGF23 was 55.7 pg/ml (reference range: 16.1-42.2 pg/mL). Eight novel mutations in the PHEX gene were identified by Sanger sequencing, including 2 missense mutations (p. Gln682Leu and p. Phe312Ser), 2 deletions (c.350_356del and c.755_761del), 1 insertion (c.1985_1986insTGAC) and 3 splice mutations (c.1700+5G>C, c.1966-1G>T and c.350-14_350-1del). Additionally, the recurrence rate after the first orthopaedic surgery was 77.8% (7/9), and five of them had their first surgery before puberty. Conclusion Our study expanded the clinical phenotypes and gene mutation spectrum of XLH and provided a reference for the optimal timing of orthopaedic surgeries.